Wildlife ranching industry: the South African flagship of a sustainable green economy - Dry, Gert C., speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Unlike American wildlife culture which is based on the belief that making money out of wildlife is immoral; the South African wildlife culture is based upon sustainable use and or commercialisation. It is trite knowledge that the value placed on game, the wildlife industry has not only restored wildlife to the land but has also enhanced and restored the genetic quality of our wildlife. The wildlife industry has grown positively, predominantly as a result of the legal trade, the exclusivity of wildlife and the hunting and tourism industry. Currently 16,8% marginal, uneconomic, semi desert agricultural land has been converted into a sustainable land use option. All private game ranches are marginal farms in economic terms that have been converted from domestic stock/crop farms into effective land-use options. These farms are not, and never have been conservation land. The South African Department of Environmental Affairs (DEA) has been highly successful with their conservation and preservation mandate with regard to national- and provincial owned parks but the implementation of a newly proposed legislative regime will seriously cripple the wildlife industry as the 'flagship' of South Africa's Green Economy. The wildlife industry proposes the development of enabling legislation that will give the wildlife industry room to grow and prosper and to be regulated as a "national competency" for the governance of the wildlife industry. The wildlife industry can assist the national growth agenda to ensure real progress. The sustainable use of South African wildlife can gain traction given evidence based research reported in various pieces of research, Macro Economic indicators for game ranching in South Africa and some specific game ranching growth initiatives.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses